Health risks and precautions for visitors to the Tokyo 2020 Olympic and Paralympic Games. Issue 22 (March 2018) - Nakamura, Sachiko; Wada, Koji; Yanagisawa, Naoki; Smith, Derek R.
Abstract: Background: In 2020, Japan will host the Tokyo Olympic and Paralympic Games in 2020 (Tokyo 2020) which will involve a large population influx from various countries to Tokyo, the most populated city in Japan. We summarize the potential health risks for visitors to Tokyo 2020, related to communicable disease risks and other health threats, based on recent national and local surveillance reports. Methods: We reviewed up-to-date surveillance reports published by the National Institute of Infectious Diseases and Tokyo Metropolitan Infectious Disease Surveillance Center. Results: Communicable disease risks for vaccine-preventable illnesses such as measles and rubella, as well as food and waterborne diseases represent the most likely risks. The risk of acquiring vector-borne diseases is considered low in Japan. On the other hand, however, heat-related illness represents a potential risk, as Tokyo 2020 is scheduled during the hottest season in Japan, with temperatures generally expected to exceed 30 °C. Conclusion: Maintaining an up-to-date routine vaccination schedule is highly recommended for visitors attending the Tokyo 2020 and appropriate hygiene measures for food and waterborne diseases as well as health promotion for heat-related illness. It may also be useful to increase the number of multilingual triage clinicians whom can be placed within emergency departments during the Tokyo 2020 to provide first contact services and coordination of emergency care among non-Japanese speaking visitors to Tokyo.